Pre-operative Imaging May Overestimate the Kidney Tumor Size - Nasseh, Hamidreza; Falahatkar, Siavash; Ghanbari, Atefeh; Bagheri Chenari, Hossein (Urology Journal, 2012)
PURPOSE: To compare the kidney tumor size on radical nephrectomy pathology specimen with size estimated by computed tomography (CT) scan and ultrasonography. MATERIALS AND METHODS: The tumor size on pathology specimen of 40 patients who had undergone radical nephrectomy at our center from March 2003 until March 2009 was compared with pre-operative CT scan and ultrasonography findings. The paired t test was used to compare the means. RESULTS: The participants included 40 patients, 25 men and 15 women, with the mean age of 64.12 ± 10.75 years (range, 42 to 79 years). All tumors were renal cell carcinoma. Mean tumor size on pathology specimen was 6.2 ± 1.1 cm. Mean tumor size estimated by pre-operative CT scan and ultrasonography was 7.34 ± 1.83 cm and 7.4 ± 1.96 cm, respectively (P = .001). Tumor stage did not affect this significant difference. There was not any significant difference between tumor size estimated by CT scan or ultrasonography (P = .39). CONCLUSION: Computed tomography scan and ultrasonography both may overestimate renal tumor size. This point must be considered in clinical staging and treatment selection. Multicenter prospective comparison is suggested.